2008
DOI: 10.1007/s10029-008-0336-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-center 10-year experience in the management of anterior abdominal wall defects

Abstract: In our single-center experience, both synthetic (Goretex patches) and natural biomaterials (dura and bovine patches) were found to be alternatives to manage these defects. The advantages and disadvantages of the alternatives are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Evidently, availability of preformed silastic silo, elective ventilation, and parenteral nutrition in developed countries has reduced the morbidity and mortality in many centres, and treatment is often completed in 2-3 weeks with good outcome. [18,24,25] In the absence of parenteral nutrition, we ensured regular haematocrit check, adequate blood and plasma transfusion, and early commencement of enteral feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, availability of preformed silastic silo, elective ventilation, and parenteral nutrition in developed countries has reduced the morbidity and mortality in many centres, and treatment is often completed in 2-3 weeks with good outcome. [18,24,25] In the absence of parenteral nutrition, we ensured regular haematocrit check, adequate blood and plasma transfusion, and early commencement of enteral feeding.…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal loss and early postnatal presurgical loss occur in the majority, although with unknown incidence. Early postoperative death is common in patients with complex cardiac anomalies, or in those having postoperative complications like respiratory insufficiency, bowel dismotility, intraabdominal and pulmonary hypertension . Late deaths are usually a complication of cardiac dysfunction, infections, or adhesive small bowel obstruction .…”
Section: Discussionmentioning
confidence: 99%
“…The contrast-enhanced test performed before the ostomy closure surgery revealed that there was malrotation in the other patient. Because of less parenteral nutrition and shorter hospital stay, primary closure of the gastroschisis is still considered an ideal correction (2)(3)(4). However, a tight closure during primary fascia repair may increase intra-abdominal pressure and the need for mechanical respiratory support.…”
Section: Discussionmentioning
confidence: 99%
“…Stomach, small and large bowel, liver, spleen and bladder may protrude through the defect (1). Gastroschisis occurs in 3:10,000 live births and has a very severe prognosis (2). Gastroschisis can be either complex abnormality having other gastrointestinal anomalies such as intestinal atresia, perforation, necrosis, volvulus or simple abnormality having no other anomalies (1,2).…”
Section: Introductionmentioning
confidence: 99%